(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Pain is the most common symptom of disease, which accompanies us from an early age. It is connected to the stimulus that it invokes and is also based on the observation of psychological interpretation of the phenomena taking place. The aim of this research is evaluation of the effect of Neocarya macrophylla leaves extracts on animal model of Pain. The pulverized leaves were extracted by maceration using 90 % methanol for 7 days and filtered to retrieve the residue known as the crude methanol leaf extract (MEL). Some part of MEL (60 g) was partitioned into fractions of different solvents with increasing polarity including chloroform (CF), ethylacetate (EF), n-butanol (BF) using liquid-liquid fractionation. Acute toxicity study was carried out to determine the LD50 of CF and it was estimated to be 565 mg/kg using Lorke’s method. Analgesic studies was carried out on extract and partitioned fractions using acetic acid-induced writhing test in mice and the results revealed that the extract and fractions of the plant has significant (p<0.05) analgesic effect with EF being the most active fraction and CF being the least active; EF demonstrated significant (p<0.05) and dose-dependent analgesic activity with 83.9, 82.5 and 73.4 % inhibition of writhes at 20, 40 and 80 mg/kg, respectively; the standard drug, piroxicam (at 10 mg/kg) had 96.5 % inhibition of writhes. Qualitative phytochemical screening on the fractions revealed the presence of some phytochemicals.Conclusively, this study indicates that the leaves of N. macrophylla contains phytochemical constituents with analgesic